PENGGUNAAN CAIRAN FESES SEBAGAI PENGGANTI CAIRAN RUMEN PADA TEKNIK IN VITRO : ESTIMASI KECERNAAN BAHAN KERING DAN BAHAN ORGANIK BEBERAPA JENIS RUMPUT - Muhammad Afdhal; Edi Erwan (Jurnal Peternakan, 2013)
The aim of this study was to reveal the potency of faecal inoculum added with sugar and urea in the in vitro technique to evaluate some grasses like Penisetum purpureum, rumput kumpeh, Setaria sphacelata dan Imperata cylindrica when compared with the rumen inoculum. The Tilley and Terry technique was applied in this study. The treatments in this experiment were rumen liquid (control), faecal inoculum, faecal inoculum + 2.5% (w/v) sugar, faecal inoculum + 2.5% (w/v) sugar and 2.5% (w/v) urea and faecal inoculum + 2.5% (w/v) urea for treatment A, B, C, D and E respectively. All grass samples were incubated with the treatments. Parameter measured were the digestibility of dry matter and organic matter. Result of these study showed that the digestibility of dry matter and organic matter of the four grasses were significant (P<0.05). Treatment A using rumen liquid was the highest in digestibility of dry matter and organic matter among other treatments.